Disulfidptosis: a novel gene-based signature predicts prognosis and immunotherapy efficacy of pancreatic adenocarcinoma - Jingyang Yin; Jian Li; Huaizhi Wang (Discover Oncology)
Abstract Disulfidptosis, a novel form of disulfide stress-induced cell death involved in tumor progression, hasn’t be well defined the function in tumor progression. And the clinical impacts of disulfidptosis-related genes (DRGs) in pancreatic adenocarcinoma (PAAD) remain largely unclear. In this study, we identified two distinct disulfidptosis subtypes and found that multilayer DRG alterations were associated with prognosis and TME infiltration characteristics. A three-gene prognostic signature was constructed to predict prognosis, and its clinical significance was characterized in the TCGA-PAAD cohort. The disulfidptosis signature was significantly correlated with prognosis, molecular subtype, CD8 T-cell infiltration, response to immune checkpoint inhibitors and chemotherapeutic drug sensitivity, and its predictive capability in PAAD patients was validated in multiple cohorts. Meanwhile, two anti-PD-L1 immunotherapy cohorts confirmed that low-risk patients exhibited substantially enhanced clinical response and treatment advantages. Furthermore, the expression patterns of DRGs were validated by quantitative real-time PCR. The expression and prognostic predictive capability of GLUT1 were verified by 87 PAAD patients from our cohort. These findings may help us understand the roles of DRGs in PAAD and the molecular characterization of disulfidptosis subtypes. The disulfidptosis signature could be a promising biomarker for prognosis, molecular subtypes, TME infiltration characteristics and immunotherapy efficacy.